2019
DOI: 10.2478/ahp-2019-0003
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the prognostic and predictive value of free light chains in patients with chronic lymphocytic leukemia – preliminary results

Abstract: Introductionκ and λ serum free light chains (sFLCs) are produced during physiological lymphopoesis by plasmocytes and B lymphocytes in a constant ratio related to heavy chains. The measurement of sFLC plays an important role in the diagnosis and monitoring of patients with multiple myeloma (MM). The first reports suggested that sFLC disturbances might have prognostic value also in patients with chronic lymphocytic leukemia (CLL). Aim of the study: The aim of the study was to evaluate the relationship between s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
0
0
0
Order By: Relevance
“…Therefore, there is a need to identify more markers that may improve the existing staging systems for better prediction and risk stratification of CLL patients at diagnosis. 2,6 Numerous studies have reported that the variety of molecular abnormalities seen in CLL patients, which are ultimately responsible for the development and progression of this illness, reflect clinical heterogeneity. 7,8 However, for cytogenetic and molecular analysis of CLL, high degree of technical and medical expertise is required for each and every case, and the process is laborious and costly.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, there is a need to identify more markers that may improve the existing staging systems for better prediction and risk stratification of CLL patients at diagnosis. 2,6 Numerous studies have reported that the variety of molecular abnormalities seen in CLL patients, which are ultimately responsible for the development and progression of this illness, reflect clinical heterogeneity. 7,8 However, for cytogenetic and molecular analysis of CLL, high degree of technical and medical expertise is required for each and every case, and the process is laborious and costly.…”
Section: Introductionmentioning
confidence: 99%